Identification of Aerodynamic Derivatives of Two Box Girder of Cable Stayed Bridge. (2015) - Sukamta; Guntorojati, Ireng
Abstract: Motion or self-induced forces can cause the aeroelastic instability phenomenon called flutter. Flutter stability is an important design criterion for long span bridges, because flutter leads to large vibration amplitudes or even the total collapse of the bridge. The flutter derivatives are the essential parameters in the estimation of the critical flutter wind speed. The aerodynamic derivatives, also known as flutter derivatives, are coefficients of the mathematical model for the aeroelastic forces. These coefficients are expressed in a non dimensional form and used to determine the flutter analysis of flexible bridges. One of the coefficients is A 2 *, this coefficient provides very useful information to judge and compare the aerodynamic stability. In order to determine the flutter derivatives, the wind tunnel tests using sectional model are very common. In the present work, the free vibration test method is used to extract the flutter derivatives of the Musi III cable stayed bridge. Estimated the A 2 * coefficient changes from negative to positive values around u/fb = 2.5, this value indicates, that the bridge was in a stable condition at the value for u/fb below 2.5. To improve the stability of the bridge, the shape of this bridge deck should be modified.